Impact of oral bisphenol A at reference doses on intestinal barrier function and sex differences after perinatal exposure in rats - Braniste, Viorica (National Academy of Sciences, 2009)
Bisphenol A (BPA), a chemical estrogen widely used in the food-packaging industry and baby bottles, is recovered in human fluids (0.1–10 nM). Recent studies have reported that BPA is hormonally active at low doses, emphasizing the debate of a risk for human health. Estrogen receptors are expressed in the colon, and although the major route of BPA exposure is food, the effects on gut have received no attention. We first examined the endocrine disrupting potency of BPA on colonic paracellular permeability (CPP), experimental colitis, and visceral sensitivity in ovariectomized rats orally exposed to 5 mg/kg/d BPA (i.e., the no observed adverse effect level), 50 μg/kg/d BPA (i.e., tolerable daily intake), or lower doses. BPA dose-dependently decreased basal CPP, with a half-maximal inhibitory dose of 5.2 μg/kg/d, 10-fold below the tolerable daily intake. This correlated with an increase in epithelial tight junction sealing, also observed in Caco-2 cells exposed to 10 nM BPA. When ovariectomized rats were fed with BPA at the no observed adverse effect level, the severity of colitis was reduced, whereas the same dose increased pain sensitivity to colorectal stimuli. We then examined the impact of perinatal exposure to BPA on intestinal permeability and inflammatory response in the offspring. In female rats, but not in male rats, perinatal BPA evoked a decrease of CPP in adulthood, whereas the proinflammatory response of colonic mucosa was strengthened. This study first demonstrates that the xenoestrogen BPA at reference doses influences intestinal barrier function and gut nociception. Moreover, perinatal exposure promotes the development of severe inflammation in adult female offspring only.